PENGARUH KELENGKAPAN SARANA PRASARANA BULUTANGKIS DALAM MOTIVASI UNTUK BERPRESTASI PADA ATLET PB. TUGU MUDA SEMARANG - Fanisa Yuliawan; Nanang Indardi; Heny Setyawati (Riyadhoh : Jurnal Pendidikan Olahraga, 2022)
Badminton is an achievement sport. Sports achievement is influenced by several factors, including endogenous factors (factors that exist within a person) and exogenous factors (environmental factors that affect a person). The background of this research is seen from the achievements that have been achieved by the PB club. Tugu Muda Semarang with several athletes managed to get achievements from the mabar championships between clubs and the Semarang regency/city level championships. This is influenced by one of the external factors, namely infrastructure. The purpose of this study was to determine the condition of PB's badminton infrastructure. Tugu Muda Semarang and the influence of the completeness of facilities and infrastructure on the motivation of athletes to excel. The research method used is a qualitative method. Data collection techniques were carried out by means of observation, interviews, and documentation. The results of this study indicate that 1). The condition of the PB club's facilities and infrastructure. Tugu Muda Semarang is good and adequate for the implementation of coaching and training, 2). The infrastructure has an effect on the training program and the athlete's motivation to practice and excel. if the athlete is not equipped with infrastructure for training, the athlete can only fantasize and it is impossible to achieve an achievement, but if the badminton infrastructure is supported, the athletes will be enthusiastic about training and motivated to achieve an achievement.